Community watershed management in semiarid India: The state of collective action and its effects on natural resources and rural livelihoods - Shiferaw, Bekele; Kebede, Tewodros A.; Reddy, V. Ratna (University of Pennsylvania Press, 2011)
Using empirical data from 87 watershed communities in semiarid India, our study has shown that collective action in watershed management can be captured through a set of variables that indicate the capacity of communities to design and enforce certain common institutional arrangements and their ability to mobilize local financial and labor resources for watershed investments. The level of collective action in terms of internal institutional capacity was affected negatively by the size of the groups (number of households and area of the village), while distance from markets and high rainfall seemed to increase it. On the other hand, collective action in terms of internal mobilization capacity decreased with rainfall, size of group, number of seasonal migrants, and distance from the seat of the local administration but increased with area of the village, flow of information within the village, and the share of land under village commons. The mobilization capacity also seems to have increased with equitable distribution of benefits and preference for employment of the rural poor and female workers. However, the results clearly show that in most watershed communities the level of collective action is very limited, indicating that only few communities have achieved higher levels of active participation of resource users in watershed programs.